2013
DOI: 10.1002/jmv.23578
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genetic diversity of norovirus among patients with acute diarrhea in Guatemala

Abstract: Noroviruses (NoVs) are a leading cause of acute gastroenteritis outbreaks and sporadic cases of diarrhea in industrialized countries. To study the prevalence and genetic diversity of NoVs in Guatemala, stool specimens were collected from hospitalized and ambulatory patients presenting with diarrhea (≥3 loose or liquid stools in a 24-hr period) who were enrolled in a prospective surveillance system in the Departments of Santa Rosa (October 2007 to August 2010) and Quetzaltenango (August 2009 to August 2010), Gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
4
17
0
Order By: Relevance
“…Our study demonstrated a low prevalence of NoV GIV.1 as described in other studies [6,22,27,28]. Both the NoV GIV.1-positive patients were hospitalized with gastroenteritis in July of 2011 from Lulong County.…”
Section: Similar and Contrasting Cases In The Literature And Discussionsupporting
confidence: 57%
“…Our study demonstrated a low prevalence of NoV GIV.1 as described in other studies [6,22,27,28]. Both the NoV GIV.1-positive patients were hospitalized with gastroenteritis in July of 2011 from Lulong County.…”
Section: Similar and Contrasting Cases In The Literature And Discussionsupporting
confidence: 57%
“…To compare the viral load between bulk stool and rectal swab specimens, the cycle threshold (Ct) values of each positive norovirus RT-qPCR result were compared. Details for the extraction of nucleic acids, Ct-value cut-offs for positive and negative specimens, and RT-qPCR detection limits are described elsewhere [11]. The laboratory testing procedures did not differ by specimen type.…”
Section: Methodsmentioning
confidence: 99%
“…This likely represents a more diverse enteropathogen landscape in the context of higher overall diarrhea incidence in high-mortality settings [2■]. Prior to rotavirus vaccine implementation, norovirus was the most frequently identified pathogen in ambulatory [4] and community [5■■] diarrhea cases in certain LMIC settings. Rotavirus was usually reported more frequently in hospitalized children [4], although up to 55% of hospital diarrhea cases demonstrated human calicivirus (norovirus and/or sapovirus) infection when evaluated with both immunologic and molecular detection methods [6,7].…”
Section: Assessing Norovirus Disease Burden In the Tropicsmentioning
confidence: 99%
“…Prior to rotavirus vaccine implementation, norovirus was the most frequently identified pathogen in ambulatory [4] and community [5■■] diarrhea cases in certain LMIC settings. Rotavirus was usually reported more frequently in hospitalized children [4], although up to 55% of hospital diarrhea cases demonstrated human calicivirus (norovirus and/or sapovirus) infection when evaluated with both immunologic and molecular detection methods [6,7]. Following successful universal rotavirus vaccination in LMICs, norovirus is recognized as the predominant pathogen in hospitalized [8■], outpatient [4], and community [9■] diarrhea cases.…”
Section: Assessing Norovirus Disease Burden In the Tropicsmentioning
confidence: 99%
See 1 more Smart Citation